Hylas, the Nymphs, Dionysos and others : myth, ritual, ethnicity : Martin P. Nilsson lecture on Greek religion, delivered 1997 at the Swedish Institute at Athens. - Sourvinou-Inwood, Christiane. (Stockholm)
421 s.